THE POLICY OF DEVELOPING FOREIGN INVESTMENT IN UZBEKISTAN AND THE POSSIBILITIES OF IMPLEMENTING THE EXPERIENCE OF DEVELOPED COUNTRIES (THE CASE OF SOUTH KOREA) - Jamshid Vohidovich Ibadullaev; Javlonbek Inatillovich Butayev (Ecominds Press, 2025)
This article analyzes the current state, existing opportunities, and challenges of the foreign investment attraction policy in the Republic of Uzbekistan. A comparative study is conducted using the successful investment policy of South Korea as an example, and the possibilities of implementing this experience in Uzbekistan are explored. The research examines the investment flows, directions, and their impact on economic growth in both countries based on tabular data analysis. Based on the findings, clear and well-founded recommendations are developed to further improve the investment environment in Uzbekistan. Key issues such as creating favorable conditions for foreign investors, liberalizing legislation, and developing infrastructure are discussed. The study evaluates the potential for ensuring sustainable economic growth in Uzbekistan through the adaptation of South Korea's investment experience.
Keywords: Foreign investment, investment policy, Uzbekistan, South Korea, foreign experience, economic growth, comparative analysis.